MEMBANGUN KOMUNIKASI YANG IDEAL DI RUANG PUBLIK - Guntoro . . (Jurnal Ilmu Komunikasi PROGRESSIO, 2020)
Communication processes occur in all places or public spaces, both among educated people and ordinary people. This is because every human being is a social creature, which can not be separated from communication with other humans as a means of meeting their needs. The communication aims to convey a message to other parties. The research in this article is qualitative, so the results of this study emphasize the meaning rather than generalization. Basically, the publicity that occurs in communication itself contains critical and comprehensive power without ignoring the logical value of the decision making process. Therefore, to build effective communication patterns, responsive responsiveness of communicators is needed in the process of communication in the public sphere.